2017
DOI: 10.1007/978-3-319-62597-3_40
|View full text |Cite
|
Sign up to set email alerts
|

Topic Study Group No. 13: Teaching and Learning of Geometry—Secondary Level

Abstract: The TSG13 program was organized to focus on the following themes:• Curricular issues in school geometry • Technological tools and environments for the study of geometry • Applications of geometry for modeling real world situations and the study of other disciplines • Connections between geometry and the study of other branches of mathematics • Connections between geometry and mathematical practices and processes such as argumentation and proof, visualization, figuration, and instrumentation • Student conceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Professional analysis of many publications [19][20][21][22] allows to assert the need for a certain rethinking by teachers of the goals and objectives of teaching geometry at school, and, as a consequence, a certain restructuring of the methodological activities of a teacher of mathematics in teaching geometry to students. Understanding the modern role and place of geometry in the formation and development of the student's personality, readiness and ability to provide appropriate conditions in the learning process of geometry are crucial for the teacher's choice of strategy and tactics of methodological activities [23].…”
Section: Discussionmentioning
confidence: 99%
“…Professional analysis of many publications [19][20][21][22] allows to assert the need for a certain rethinking by teachers of the goals and objectives of teaching geometry at school, and, as a consequence, a certain restructuring of the methodological activities of a teacher of mathematics in teaching geometry to students. Understanding the modern role and place of geometry in the formation and development of the student's personality, readiness and ability to provide appropriate conditions in the learning process of geometry are crucial for the teacher's choice of strategy and tactics of methodological activities [23].…”
Section: Discussionmentioning
confidence: 99%
“…In Krutetskii's studies with 34 mathematically talented students, 23 exhibited harmonic reasoning. In geometric instruction, teaching practice associated with argumentation encourages connections with other branches of mathematics and coordinates perceptual with numerical or symbolic skills [1,45,54,55]. Research has nonetheless revealed student preference for logical-verbal over visual processing [53], which is observed in fewer students [56].…”
mentioning
confidence: 99%